Sericin/polyvinyl alcohol hydrogel optimization for enhanced angiogenesis: a promising strategy for treating chronic osteomyelitis - Chayanee Noosak; Pavarish Jantorn; Suvimol Surassmo; Sittichat Chukaew; Jirut Meesane; Dennapa Saeloh Sotthibandhu (PLoS ONE, 2025)
Chronic osteomyelitis, often accompanied by bone loss, requires an adequate angiogenic response for bone regeneration. Loading growth factors into a drug vehicle to promote angiogenesis can address this challenge. In a previous study, we demonstrated the potential of sericin/polyvinyl alcohol (PVA) hydrogel as a functional biomaterial carrier for osteomyelitis treatment. In this study, we optimized sericin/PVA hydrogel for enhanced angiogenesis by supplementing sericin nanoparticles as vascular endothelial growth factor (VEGF) nanocarriers. Sericin nanoparticles, 284.20 ± 13.20 nm in size, exhibited a spherical morphology with 86% VEGF encapsulation efficiency. After integrating VEGF-loaded sericin nanoparticles, the hydrogel was coated with 0.1% and 1% gelatin, and its physical and mechanical properties were assessed. Coating the hydrogel with gelatin enhanced its swelling properties, providing an appropriate degradation rate to support bone regeneration and angiogenesis, and improve mechanical properties. The uncoated hydrogel and hydrogels coated with 0.1% and 1% gelatin exhibited burst release rates of 70%, 60%, and 45% with cumulative release rates on day 14 measured at 76%, 67%, and 57%, respectively. The hydrogels were biocompatible with MC3T3-E1 osteoblastic cell lines and human umbilical vein endothelial cells (HUVEC). The gelatin-coated hydrogels also promoted cell attachment of HUVEC cells. Gelatin-coated hydrogels containing VEGF-loaded sericin nanoparticles were evaluated for their bioactivity on HUVEC cell proliferation. After a 14-day treatment, cell proliferation in 0.1% gelatin-coated hydrogel was significantly higher than in 1% gelatin-coated hydrogel, with over a 160% increase. The expression levels of genes related to angiogenesis were quantitatively examined and results suggested that the hydrogels affected the eNOS pathway to promote angiogenesis. Despite optimization efforts, the sericin/PVA hydrogel maintained effective antibacterial activity against Gram-positive and Gram-negative bacteria. The enhanced sericin/PVA hydrogel showed promise as a novel implant biomaterial for treating chronic osteomyelitis, particularly by promoting angiogenesis.